FEATURES OF THE USE OF ENZYMES IN FOOD TECHNOLOGIES TO INCREASE PRODUCTION EFFICIENCY - KOVAL, EUGENE; SOLOMON, ALLA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In the modern food industry, various food additives are actively used to improve the quality of the finished product. Enzymes are extremely effective biological catalysts of protein nature, which, acting in a strictly defined sequence, increase the speed of chemical reactions hundreds of times. The use of enzymes has now become the most important industrial principle of food technology improvement. The use of enzymes in food technologies is at the stage of active development, their range and the functions they can perform in food systems are expanding. The effectiveness of the introduction of enzymes as technological additives-improvers is beyond doubt. The article is devoted to highlighting the peculiarities of the introduction of enzymes into food products of the bakery, confectionery, sugar, meat, alcohol, starch and molasses industries, etc. It is shown that the use of enzymes makes it possible to intensify technological processes, increase the yield and quality of products. The main functions of enzymes in food technology are acceleration of biochemical processes, improvement of organoleptic properties of products, increase of yield of beverages, meat, bread and confectionery products, increase of extractability of beverages, intensification of deep hydrolysis of starch and proteins and milk sugar - lactose, prevention of oxidation processes and development aerobic microorganisms, enrichment of valuable nitrogenous nutrition of yeast wort; combating non-biological clouding of beer, adjusting the technological characteristics of flour, strengthening the gluten framework and improving plasticity in frozen dough, ensuring the rheological characteristics of puff pastry and the necessary consistency at high sugar concentrations in fondant candies, caramel, praline, etc. It was concluded that the achievement of high product quality, high product yield and intensification of technological processes, which directly affects the production efficiency, are practically impossible without the use of technological additives - enzymes.